Clinical importance of recently discovered gene variants in colon cancer recurrence and prognosis. (April 2014) - Sebio, Ana; Lenz, Heinz-Josef
SUMMARY : Colorectal cancer survival has increased over the past few years, mainly due to the advances in the metastatic setting. Nonetheless, in the adjuvant scenario, minor improvements have been made, as the tumor's anatomopathological features remain to be most important factors for predicting the risk of recurrence and the prognosis. A deeper understanding of the molecular mechanisms involved in colorectal carcinogenesis, progression, invasion and metastasis development, have laid the groundwork for the search of genetic biomarkers that can help identify patients at a higher risk of recurrence. Common germline variants in genes within molecular pathways responsible for cancer development and progression have proven to influence the probability of relapse and the patient's prognosis. Here, we systematically review the relevance of genetic variants as prognostic biomarkers in colorectal carcinoma.